Endhorpin Massage and Pregnancy Exercise as a Method to Relieve Lower Back Pain in Trimester III Pregnant Women - Yusni Podungge (Health Notions, 2019)
Pregnancy is a happy thing for every husband and wife but sometimes complaints arise during pregnancy, one of them that is very annoying is back pain problems when pregnant. Back pain when pregnant is usually experienced by women in certain time of the pregnancy, usually happens often in trimester 3 pregnancy. The purpose of this research is to know the difference of pregnancy exercise effectiveness with endhorpin message to decrease in lower back pain in trimester III pregnancy at Sipatana Public Health Center. This research type was quasi experiment by using the method of pre and post test with two group design. The total samples were 30 people. The result of bivariate analysis was pregnancy exercise (p = 0.000) and endhorpin message (p = 0.000) which (p